2018
DOI: 10.1155/2018/8187693
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Horizontal Bearing Capacity of Vertical Steel Floral Tube Micropiles with Double Grouting

Abstract: This paper examines the performance of a novel technology, vertical steel floral tube micropiles with double grouting. It is the combination of micropile technology and double grouting technology. A large-scale model tank was applied to impart horizontal bearing capacity, and the slope soil pressure and flexural performance of the micropile were investigated under four experimental conditions. The peak grouting pressure during the double grouting process was defined as the fracturing pressure of the double gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…This improves the physical and mechanical properties of soil at the tip and around the pile, thus enlarging the bearing capacity of the pile foundation [21,22]. In the process of grouting, piles and soil between piles form a composite foundation [23] and produce an extrusion effect [24,25], the physical and mechanical properties of the composite foundation inter-pile soil have been greatly improved [26,27]. In addition, new techniques, such as biological grouting, have been increasingly applied to improve the strength of soil between piles [28].…”
Section: Introductionmentioning
confidence: 99%
“…This improves the physical and mechanical properties of soil at the tip and around the pile, thus enlarging the bearing capacity of the pile foundation [21,22]. In the process of grouting, piles and soil between piles form a composite foundation [23] and produce an extrusion effect [24,25], the physical and mechanical properties of the composite foundation inter-pile soil have been greatly improved [26,27]. In addition, new techniques, such as biological grouting, have been increasingly applied to improve the strength of soil between piles [28].…”
Section: Introductionmentioning
confidence: 99%
“…Feng [12] proposed a theoretical calculation formula for landslide reinforcement by perforated pipe micropile. Wang and Shang [13] studied the double grouting technology of the perforated pipe micropile and proved that this technology can effectively improve the bearing capacity of micropile through experiments. Qiang et al and He et al [14,15] have shown that the perforated pipe micropile has a beneficial effect on controlling the displacement of landslide soil, and high pressure grouting can improve the horizontal ultimate bearing capacity of the perforated pipe micropilereinforced landslide.…”
Section: Introductionmentioning
confidence: 99%